1982
DOI: 10.1055/s-2007-971236
|View full text |Cite
|
Sign up to set email alerts
|

Brine Shrimp: A Convenient General Bioassay for Active Plant Constituents

Abstract: A method, utilizing brine shrimp (Artemia salina Leach), is proposed as a simple bioassay for natural product research. The procedure determines LC (50) values in microg/ml of active compounds and extracts in the brine medium. Activities of a broad range of known active compounds are manifested as toxicity to the shrimp. Screening results with seed extracts of 41 species of Euphorbiaceae were compared with 9KB and 9PS cytotoxicities. The method is rapid, reliable, inexpensive, and convenient as an in-house gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
3,088
5
550

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,071 publications
(3,683 citation statements)
references
References 1 publication
40
3,088
5
550
Order By: Relevance
“…It has been suggested that the Schiff base with nitrogen and oxygen donor systems inhibit enzyme activity, since the enzymes which require these groups of their activity appear to be especially more susceptible to deactivation by metal ions on coordination. Moreover, coordination reduces the polarity [15,16] of the metal ion mainly because of the partial sharing of its positive charge with the donor groups [17,18] within the chelate ring system formed during coordination. This process, in turn, increases the lipophilic nature of the central metal atom, which favors its permeation more efficiently through the lipid layer of the microorganism [19][20][21] thus destroying them more aggressively.…”
Section: Pharmacology Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the Schiff base with nitrogen and oxygen donor systems inhibit enzyme activity, since the enzymes which require these groups of their activity appear to be especially more susceptible to deactivation by metal ions on coordination. Moreover, coordination reduces the polarity [15,16] of the metal ion mainly because of the partial sharing of its positive charge with the donor groups [17,18] within the chelate ring system formed during coordination. This process, in turn, increases the lipophilic nature of the central metal atom, which favors its permeation more efficiently through the lipid layer of the microorganism [19][20][21] thus destroying them more aggressively.…”
Section: Pharmacology Resultsmentioning
confidence: 99%
“…The synthesized Schiff base and its Co(II), Ni(II) and Cu(II) complexes were screened for their cytotoxicity (brine shrimp bioassay) by using the protocol of Meyer et al [17]. Brine shrimp (Artemia salina leach) eggs were hatched in a shallow rectangular plastic dish (22 Â 32 cm) filled with artificial seawater, which was prepared with a commercial salt mixture and double distilled water.…”
Section: In-vitro Cytotoxicitymentioning
confidence: 99%
“…From a pharmacological point, a good relationship has been found with the brine shrimp lethality test to detect antitumoral compounds in terrestrial plant extracts [5,9,10] . Then, root extract as the most toxic part of L. camara is more potential to anticancer phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactivity of the L. camara extracts was measured by the brine shrimp lethality test [5] . Samples were dissolved in DMSO and diluted with artificial seawater (concentration 100 毺 g/mL).…”
Section: Brine Shrimp Assaymentioning
confidence: 99%
“…Brine shrimp lethality bioassay was carried out according to Meyer et al [24] to investigate the cytotoxicity of the extract. The dried extract preparation was redissolved in DMSO to obtain a solution of 10 mg/mL of the extract for toxicity test.…”
Section: Brine Shrimp Lethality Bioassay Of the Extractmentioning
confidence: 99%